UV/VIS SPECTROPHOTOMETRY OF METHYLEN BLUE CONVERSION FROM SULFIDE AND INFRARED SPECTROPHOTOMETRY OF METAL SULFIDE - Delvy
Pollution is one of main problems which cause a bad influence to environmental condition and human living in it. Improvement of public awareness to value of healthy condition makes people start to think critically about any problems concern on healthiness. Therefore, air pollution that recently gives negative effects to society healthiness, have got many attention from public. One of the most poisonous air pollutants is sulfide gas. This gas is produced from both vehicle combustion with fuel containing sulfide and exhaust gas-plants that use sulfur as a raw material. Unfortunately, hydrogen sulfide is very dangerous because it can cause inflammation, loss of sensor senses and death at high concentration. Many research which is concern on determination and measurement of concentration of sulfide gas and dissolved sulfide have been done. Currently, spectrophotometry method to determine sulfide gas concentration and dissolved sulfide in form of methylene blue complex, is thought as a sensitive method. In this research, UV-VIS spectrophotometry analysis of methylene blue resulted from gas conversion and dissolved sulfide was studied. In addition, quantitative analysis by using infrared spectrophotometry from metal sulfide absorption, CdS and CuS, was done. Based on the results of spectrophotometry study of methylene blue, efficiency of methylene blue formation from sulfide solution was 30.66 ± 18.06%, while efficiency of methylene blue conversion from sulfide gas was 13.20 ± 6.50%. From previous research done by Fatma in 1989, sulfide gas recovery from trapping by Cd2+ solution was 76.28%, compared to methylene blue conversion from sulfide solution. Whereas, recovery of sulfide gas in this research, in which sulfide gas trapping done by solid adsorbent (filter paper contain Cd2+), was 64.10±11.21%. Measurement result of methylene blue in filter paper spectrum by DRS-IR showed that the presence of methylene blue in filter paper did not produce new absorption band, but decreased absorbance from filter paper. Infrared spectrum of CdS revealed that there were absorption band from vibration of H2O at 3606 cm-1, vibration of SO42- at 1010 cm-1, 1114 cm-1, and 619 cm-1, and metal-ligand vibration (vCd-S) at 472 cm-1 and 524 cm-1. CdS absorptivity values were 0,704 (1/mm%w/w) at 1116.05 cm-1 and 0,344 (1/mm%w/w) at 620.23 cm-1. Consequently, quantitative analysis was better performed on the wavenumber of 1116.05 cm-1. Calibration curve equation at 1116.5 cm-1 was A = 0.588 [CdS] + 0.124 and at 620.23 cm-1 was A = 0.277 [CdS] + 0.033. The infrared spectrum of CuS depicted that there were absorption band from vibration of H2O at 3421 cm-1 and 3516 cm-1, vibration of SO4-2 at 1093 cm-1, 1161 cm-1, and 1199 cm-1, and metal-ligand vibration (vCu-S) at 426 cm-1, 453 cm-1, 532 cm-1 and 506 cm-1. Absorptivity value of CuS at 426.446 cm-1 was 0,452 (1/mm%w/w) and at 506.546 cm-1 was 0,297 (1/mm%w/w). Therefore, quantitative measurements were better carried out at 426.446 cm-1. Calibration curve equation for the wavenumber 426.446 cm-1 was A = 0.285 [CuS] + 0.025, while A = 0.188 [CuS] + 0.002 was for wavenumbers at 506.546 cm-1. All calibration curves depicted an increasingly wide confidence interval on the measurement of higher concentration. Therefore, by analyzing sample at approximately low concentration, below 1% w/w, we could get both small uncertainty and high precision. From research about influence of another sulfide metal to sulfide metal measurement, we conclude that there was significant difference of real concentration of CdS to measurement result, using either calibration curve or absorptivity data. Therefore, measurement of CdS concentration with influence of CuS is not specific. Measurement result of CuS concentration at 506.46 cm-1 closer to real result better than measurement at 426.446 cm-1. From obtained research results, CdS in mixture did not influence measurement of CuS concentration at wavelength of 506.546 cm-1. As a result, this peak is a specific peak for CuS and then can be used to determine CuS concentration by the presence of another sulfide metal, in this case is CdS.